Application of the commercial ion exchange membranes in the all-vanadium redox flow battery - Hwang, Gab-Jin; Kim, Sang-Won; In, Dae-Min; Lee, Dae-Yeop; Ryu, Cheol-Hwi (한국공업화학회, 2018)
Three commercial anion exchange membranes and two commercial cation exchange membranes were tested to use as a separator in the all-vanadium redox flow battery (VRFB). Membrane properties such as an ionic conductivity and a permeability of each vanadium ion were evaluated. Ionic conductivities decreased in the order: Nafion117 approximate to APS > NEPEMI15 > FAP-PP-475 > FAP-PE-420. An anion exchange membrane had a low permeability of each vanadium ion compared to a cation exchange membrane. Energy efficiencies of VRFB using the commercial ion exchanges membrane had almost the same value in the range of 76.0-78.7%. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.